Costly Concessions: The Effect of Fragmentation of Self-Determination Movements on State Repression - La Spada, Eleonora Miriam (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2021)
There is a great variation in the way governments respond to dissent. Governments responses to internal challengers vary from peaceful accommodation to various forms of repression. This variation has important implications for both dispute resolution and how conflicts unfold. This thesis focuses in particular on the use of state repression over self-determination disputes. Its main objective is to investigate the relation between the internal structure of self-determination movements and the use of state repression. I contend that the internal structure of challenging movements, and specifically their internal degree of fragmentation, affects the use of repressive actions by the government when facing self-determination disputes. The use of internal fragmentation of challengers as an explanatory variable is a novel approach within the literature of repression and dissent. The extant literature has widely analyzed state repression as a response to dissent, yet it has so far overlooked that the choice to resort to repressive actions may also depend on the internal fragmentation of the challengers, which are rarely if ever homogeneous actors. This leaves this large strand of literature incomplete. In the field of ethnic conflict dynamics, instead, the role of the disputants internal structures is already acknowledged and the applicability of fragmentation theory for understanding conflict onset is now well-documented. Thus, focusing on the internal fragmentation of opposition movements to investigate dissent-repression interaction can help us better understand further aspects and incentives of the use of repression by governments against internal challengers, which remains improperly explained by current theories. In this dissertation, drawing on the theory of actor fragmentation developed in civil conflict studies, I propose a mechanism, to investigate the use of repression over self-determination disputes within the context of state-dissident interaction. My central argument is that higher degrees of fragmentation make negotiations more difficult ex ante due to frictions and disagreements among the different factions: these frictions are exacerbated if the government only partially accommodates the requests of an internally divided movement. Hence, within-movement fragmentation constrains the ability of governments to use concessions to resolve the dispute and instead increases incentive to repress. The dissertation comprises three core papers. Each paper investigates the relationship between the internal fragmentation of Self-determination (SD) movements and the use of state repression at different levels of analysis. The first two papers (Chapters 2 and 3) are Large-N quantitative analyses, while the third paper (Chapter 4) is dedicated to a qualitative case analysis of the Bodo movement in Assam via process tracing. A structure comprised of both quantitative and qualitative analyses provides both external validity and tests for the causal mechanism proposed. Chapter 2 analyzes the effect of the internal fragmentation of SD movements on the level of government repression at the national level on a sample of 72 countries between 1981 and 2005. The units of analysis are country-year observations. Here, the main objective is to investigate the effect of the overall level of within-movement fragmentation the degree of fragmentation aggregated across SD movements on the overall level of state repression. The findings show that higher degrees of overall fragmentation are associated with higher levels of overall state repression. Results hold across the specification models estimated. Chapter 3 investigates the effect of within-SD movements on the use of state repression at the movement level. The unit of analysis, here, is the country-movements-years observations. in 72 countries between 1996 and 2005. Alongside the main hypothesis that higher degrees of within-movement fragmentation lead to a greater level of state repression, two ancillary hypotheses are also tested in the chapter: The effect of within-movement fragmentation on state repression is relatively greater if there are active violent militants within the movement (H2), and the effect of within-movement fragmentation on state repression is relatively smaller if there is one or a few dominant factions within the movement (H3). I also developed two formal bargaining models to strengthen the clarity and support the consistency of the causal mechanism proposed. I empirically test the theoretical argument on a sample of 118 self-determination movements and 72 countries from 1996 to 2005. The regression results support the hypotheses and hold across several different specification models. Chapter 4, finally presents a qualitative case study of the Bodo movement in Assam (Northeast of India) using process tracing techniques, with the aim of establishing sufficient confidence in the internal validity of the regression analyses and assuaging fears of endogeneity issues. The aim is to provide a more fine-grained understanding of the mechanism linking the level of within-movement fragmentation and the use and levels of state repression. Testing, and support for, the existence of such a mechanism would in turn also increase the overall credibility of the theory while also providing deeper explanations of the linkages. The analysis shows four main results: i) internal fragmentation of the movement led to repressive responses by the government; this effect seems to be strengthened, but not exclusively driven, by the presence of violent factions; ii) the government was willing to negotiate concessions when the movement attempted to overcome factional interests and reached some sort of cohesiveness; iii) the concessions given to the movement further fragmented it and led dissatisfied factions to escalate the conflict; iv) in turn, the government had even more incentives to pursue high levels of repression against the movement. Chapter 5 revisits and discusses the findings of the earlier chapters, and identifies wider policy implications. The thesis, in particular highlights the relevance of both the applicability of the fragmentation theory in the study of dissent-repression dynamics and disaggregating the levels of analysis, as done in Chapters 3 and 4. Disaggregated data allow for more fine-grained analyses and direct test of the plausibility of the causal mechanisms of state repression against individual challengers (SD movements). Overall, the thesis shows that the proposed mechanism provides evidence of the fragmentation theory approach in explaining the use of state repression over SD disputes. Moreover, and importantly, though the focus of this analysis is on internally divided SD movements, the mechanism I proposed here can be potentially applied to any fragmented opposition movement. The findings of this dissertation would hence be useful and additional insights for various literatures of social science, beyond the investigation of dissent-repression interaction or civil conflict dynamics, and they can further contribute to our understanding of individual and collective behaviors.
APPROVED
Keywords: state repression; self-determination movements; fragmentation; conflict dynamics; ethnic conlficts; panel analysis